2018
DOI: 10.1017/s0022226718000294
|View full text |Cite
|
Sign up to set email alerts
|

Frequency effects in Subject Islands

Abstract: This work provides evidence that Subject Island violation effects vanish if subject-embedded gaps are made as frequent and pragmatically felicitous as non-island counterpart controls. We argue that Subject Island effects are caused by the fact that subject-embedded gaps are pragmatically unusual – as the informational focus does not usually correspond to a dependant of the subject phrase – and therefore are highly contrary to comprehenders’ expectations about the distribution of filler–gap dependencies (Chaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 108 publications
(222 reference statements)
1
17
0
Order By: Relevance
“…In addition, we observed that extractions from subjects that leave a preposition stranded are much worse than corresponding preposition stranded extractions from objects. This result replicates previous results showing that extractions from objects are rated better than extractions from subjects (Polinsky et al, 2013;Sprouse et al, 2016, Chaves & Dery, 2019.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, we observed that extractions from subjects that leave a preposition stranded are much worse than corresponding preposition stranded extractions from objects. This result replicates previous results showing that extractions from objects are rated better than extractions from subjects (Polinsky et al, 2013;Sprouse et al, 2016, Chaves & Dery, 2019.…”
Section: Discussionsupporting
confidence: 91%
“…Here we sought to replicate others' earlier results showing that extractions from objects are rated better than extractions from subjects (Polinsky et al, 2013;Sprouse et al, 2016;Chaves & Dery, 2019) with preposition stranding.…”
Section: Experiments 2: English Relative Clauses Involving Extraction...mentioning
confidence: 80%
See 2 more Smart Citations
“…Which property makes sentences prone to satiation remains unclear. Explanations in the literature range from structural properties within generative syntax (Snyder [ 5 ]: 579 classical “subjacency” effects in the sense of Chomsky [ 6 ]) to sentence processing difficulty (as in, e.g., Chaves & Dery [ 7 , 8 ]) to issues of comprehension fluency (e.g., Zervakis & Mazuka [ 9 ]).…”
Section: Introductionmentioning
confidence: 99%